Neologising misogyny: Urban Dictionary's folksonomies of sexual abuse. (May 2020) - Ging, Debbie; Lynn, Theodore; Rosati, Pierangelo
Web 2.0 has facilitated a particularly toxic brand of digital men's rights activism, collectively known as the Manosphere. This amorphous network of online publics is noted for its virulent anti-feminism, extreme misogyny and synergies with the alt-right. Early manifestations of this phenomenon were confined largely to 4/Chan, Reddit and numerous alt-right forums. More recently, however, this rhetoric has become increasingly evident in Urban Dictionary. This article presents the findings of a machine-learning and manual analysis of Urban Dictionary's entries relating to sex and gender, to assess the extent to which the Manosphere's discourses of extreme misogyny and anti-feminism are working their way into everyday vernacular contexts. It also considers the sociolinguistic and gender-political implications of algorithmic and linguistic capitalism, concluding that Urban Dictionary is less a dictionary than it is a platform of folksonomies, which may exert a disproportionate and toxic influence on online discourses related to gender and sexuality.